A specialist service for the administration of ophthalmic benefit
1929-01 1929 1920s 1 page A SPECIALIST SERVICE FOR THE ADMINISTRATION OF OPHTHALMIC BENEFIT. Arrangements have been made by the National Ophthalmic Treatment Board, composed for the time being of representatives of the British Medical Association and the Association of Dispensing Opticians, for the provision of a specialist ophthalmic service, as recommended in the Majority Report of the Royal Commission on National Health Insurance, under which members of Approved Societies may obtain a day or evening consultation with an ophthalmic surgeon at his private consulting rooms at a fee of 10/6, and the skilled dispensing and fitting of the requisite glasses by specialist dispensing opticians. The prices of all glasses provided under the Scheme are fixed, the quality being standardised throughout, thus safeguarding the individual member. Prices, which include best quality lenses of any power, are as follows :— s. d. White metal rimmed spectacles, rimmed eyeglasses and rimless eyeglasses 7 6 1/10th 10 ct. Rolled Gold rimmed spectacles, rimmed eyeglasses and rimless eyeglasses 15 0 6 Patterns of Imitation Shell Frames, and 1/10th 10 ct. rimless spectacles... (plus the ophthalmic surgeon's fee of 10/6 in each case.) 22 6 It should be noted that the power of the lenses does not affect the price — all powers are provided for in each of the three scales, thus simplifying the procedure very considerably. Approved Societies may, if they care to do so, adopt one of the three scales for all their members, but where this is not possible a grant may be made by the Approved Society towards the total cost, the balance being paid by the member. The procedure under this Scheme is very simple. The Society authorises the Board to provide ophthalmic treatment, stating the amount of the grant they are prepared to make. The member is examined by an ophthalmic surgeon, the glasses where they are necessary are provided, the member's receipt being sent to the Society as a claim for payment of the amount authorised. Numbered books of forms of authority will be issued to Approved Societies on request. In those cases where the Ophthalmic Surgeon does not prescribe glasses the charge to the Approved Society is reduced to 10/6 only. This Service will come into operation in February in the towns given in the enclosed list. Arrangements have been made to extend the Service to districts where the demand of Approved Society members requires it. Full details of the Scheme are enclosed. National Ophthalmic Treatment Board. January, 1929 292/841.4/1/60